English language education among young learners in East Asia: A review of current research (2004–2014). (18th June 2015) - Butler, Yuko Goto
Abstract : The teaching of foreign languages to young learners is growing in popularity around the world. Research in this field, particularly of English as a second/foreign language education in East Asia, is a relatively new area of empirical inquiry, and it has the potential to make significant contributions to child second-language acquisition (Child-SLA) theory building, research methodologies, and policies in East Asia and beyond. This article reviews relevant peer-reviewed literature on English education among young learners in East Asia (China, Japan, South Korea, and Taiwan). I begin by reviewing policy literature to illustrate the social and policy contexts of early English education, identifying major policy-related concerns. Next, I review empirical studies of English learning and teaching, organizing them by their relevance to the previously identified policy concerns. The article concludes with suggestions for future research.